Acute effects of pre-workout supplement on aerobic and anaerobic performance in basketball players - O. Çetin; M.N. Yaşar; B. Demirtaş; M. Beyleroğlu; S. Eker; A.C. Gürkan (Physical Education of Students, 2018)
Background and aim of the study : In recent years, the use of ergogenic aid has become widespread in order to improve performance among the athletes and to achieve success more easily. Pre-workout nutritional supplements that attract the attention of many athletes as a legal ergogenic aid are used by both aerobic and anaerobic branch athletes. The aim of this study is to examine the acute effect of the pre-workout supplement on aerobic and anaerobic performance in basketball players. Material and Method: Twenty male college basketball players who have played regularly at least for 5 years participated in the study voluntarily (mean ± SD 22.00 ± 1.70 years, height 1.83 ± 0.07 cm, weight 85.15 ± 10.78 kg, BMI 25.32 ± 3.10). Double-blind placebo-controlled, cross-over method was used for the collection of data. The players were divided into two groups as placebo (PL, n= 10) and pre-workout (PRW, n= 10). Placebo and pre-workout groups were replaced 48 hours after the initial measurements and the same tests were repeated. The pre-workout group was given 17 gr (Bigjoy Predator) in 200 mg of additive-free juice 1 hour before the test, only 200 mg of additive free juice was given to the placebo group. Countermovement Jump (CMJ) and Running-Based Anaerobic Sprint Test (RAST) were used to measure the anaerobic performance of the athletes, and Yoyo Intermittent Recovery Test 1(Yo-Yo IRL1) was used to measure aerobic capacities. Results: A significant difference was found concerning the Countermovement Jump (CMJ) test results (p= 0, 004), Relative peak power (p= 0.001) and Relative average power (p= 0.012) values obtained from RAST test data. There was no significant difference in fatigue index (p = 0.79) and VO2 max (p= 0.492) values. Conclusion: While pre-workout supplementation has an acute effect on anaerobic power data, it has been observed that there is no acute effect on the data obtained from fatigue index and aerobic endurance test.